2018
DOI: 10.1186/s12905-018-0528-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with menstrual cycle irregularity and menopause

Abstract: BackgroundA regular menstrual cycle is an important indicator of a healthy reproductive system. Previous studies reported obesity, stress, and smoking as the factors that are associated with irregular menstruation and early menopause. However, the integrative effects of these modifiable risk factors have not been fully understood. This study aimed to investigate the modifiable risk factors of menstrual cycle irregularity and premature menopause, as well as their individual and combined effects among adult wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
4
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 49 publications
3
84
4
4
Order By: Relevance
“…In our present study we did not nd any difference in both the length of menstrual cycles and the length of menses among groups according to BMI categories, although previous studies found such association [2][3][4][5][6][7] . Again, the difference could be explained by the age of women who participated in these studies.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In our present study we did not nd any difference in both the length of menstrual cycles and the length of menses among groups according to BMI categories, although previous studies found such association [2][3][4][5][6][7] . Again, the difference could be explained by the age of women who participated in these studies.…”
Section: Discussioncontrasting
confidence: 84%
“…To date, studies about the association between BMI and menstrual blood loss are very limited since most studies investigated the association between BMI and irregular menstrual cycle lengths [2][3][4][5][6][7][8] . A previous study reported a higher incidence of heavy menstrual blood loss and longer menstrual cycle and irregular menstrual cycle in overweight women 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Aforementioned menstrual disorders had a negative impact on the quality of life as it resulted in class absenteeism, social restrictions and limited academic, sports and daily activities (Unsal et al, 2010). An increased risk of menstrual disorders has been associated with obesity, smoking, coffee consumption, menstrual bleeding >7 days and a positive family history of dysmenorrhea and PMS (Bae et al, 2018;Unsal et al, 2010). Psychological stress is also known to be independently associated with premenstrual symptoms and the experience of irregular menstrual cycles among college students (Rafique and Al-Sheikh, 2018;Yamamoto et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We were also interested if there was any additional impact of nonneurological comorbidities or chronically used medications, as the prevalence of menstrual abnormalities in general population is influenced by smoking, obesity, and chronic stress. 8 …”
Section: Introductionmentioning
confidence: 99%